2021
DOI: 10.52082/jssm.2021.391
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of High-intensity Resistance Exercise on Cognitive Function

Abstract: The purpose of the present study was to examine the influence of an acute bout of high-intensity resistance exercise on measures of cognitive function. Ten men (Mean ± SD: age = 24.4 ± 3.2 yrs; body mass = 85.7 ± 11.8 kg; height = 1.78 ± 0.08 m; 1 repetition maximum (1RM) = 139.0 ± 24.1 kg) gave informed consent and performed a high-intensity 6 sets of 10 repetitions of barbell back squat exercise at 80% 1RM with 2 minutes rest between sets. The Automated Neuropsychological Assessment Metrics (ANAM) was comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The ANAM battery of cognitive tests was chosen based on previous evidence that it is a valid and reliable tool to assess cognitive function in military adult population (Levinson et al, 2005;Reeves et al, 2007). Our group recently established that high-intensity resistance exercise may elicit domain-specific influences on cognitive function utilizing the ANAM core test battery (Anders et al, 2021). Performance in several tests were improved throughout the 6-week study, showing familiarization, and learning of specific tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The ANAM battery of cognitive tests was chosen based on previous evidence that it is a valid and reliable tool to assess cognitive function in military adult population (Levinson et al, 2005;Reeves et al, 2007). Our group recently established that high-intensity resistance exercise may elicit domain-specific influences on cognitive function utilizing the ANAM core test battery (Anders et al, 2021). Performance in several tests were improved throughout the 6-week study, showing familiarization, and learning of specific tasks.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that physical exercise should be moderate [ 9 ], since high-intensity exercise may depress cognitive abilities [ 74 , 75 ]. Our results obtained from the Borg scale, a measure of perceived exertion and dyspnea associated with exercise, constitute an indirect measure of exercise intensity, which was perceived in average terms by both groups as having a light to hard intensity, and not being very hard.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study was conducted to investigate the effect of RE on RT or to compare the effects of these different exercise modalities in these individuals. In individuals with TD, both AE (Anders et al, 2021; Hsieh, Chang, Fang, & Hung, 2016) and RE (Kendall et al, 2021: Formenti et al, 2020) have been shown to produce RT enhancement. Although the explicative mechanisms were not explored in the current study, according to the literature, several explanations were proposed.…”
Section: Discussionmentioning
confidence: 99%